Indicadores de lesão e inflamação muscular em atletas -revisão integrativa da literatura - Hellen Rodrigues Teixeira Silva Daameche; Michelle Zampieri Ipolito; João Paulo Chieregato Matheus (UniEVANGÉLICA, 2018)
Objective:to search the available literature, indications for the release of biomarkers of injury and muscle inflammation triggered by physical exercise. Data sources:A bibliographical survey was performed in the MEDLINE and LILACS databases, using the terms: indicators, injuries, inflammation, muscle and athletes. Data synthesis:the studies evidenced that there is an increase in the serum activity of the lesion indicators and muscle inflammation after high intensity exercises. Conclusions:The results of the study corroborate both the implementation of training strategies that aim to improve the performance of the athlete and the prevention of overloads to reduce the risk of sports injuries